Influence Capital Structure, Liquidity, Profitability and Company Size on the Company's Corporate Value Food and Drinks on the Indonesian Stock Exchange 2019-2022 - Putri, Riska Sabilla Ananda; Sitanggang, Yessa Teshalomika Br; Damanik, Wita Astrina; Pane, Afrizar; Harahap, Riva Ubar (Lembaga Riset Ilmiah, 2024)
This study aims to determine influence profitability, liquidity and capital structure to mark company to company food and beverages listed on the Indonesian Stock Exchange during 2019-2021 period. Determination method sample by method quantitative. Number of companies that made sample in 3 yearfinal is 20 company, so that amount sample study is 60 company. Technique analysis data This use tool measuring that is SPSS. Results study This show that variable profitability as measured by Return on Asset (ROA) ratio has an effect to mark company (PBV). Whereas variable liquidity Which measured with ratio Current Ratio (CR) and capital structure as measured by the Debt to Equity Ratio (DER) ratio have no effect to mark company (PBV)